Characteristics of NAFLD Based on Hypopituitarism - Kazuhisa Kodama; Atsuhiro Ichihara; Yasufumi Seki; Yuichi Ikarashi; Takaomi Sagawa; Tomomi Kogiso; Maiko Taniai; Katsutoshi Tokushige (Canadian Journal of Gastroenterology and Hepatology)
Background. Hypopituitarism and hypothalamic disorders, which induce central obesity and appetite disorder, are associated with nonalcoholic fatty liver disease (NAFLD). We retrospectively analyzed the clinical features of NAFLD patients with hypopituitarism. Patients. We examined the cases of 15 NAFLD patients with hypopituitarism (mean age, 39.4 years; males/females, 11/4). The causes of hypopituitarism were surgical in eight cases (six with craniopharyngioma and two with prolactinoma) and nonsurgical in seven cases, including unexplained hypopituitarism in five cases, Sheehan syndrome in one case, and one case that occurred after the radiation therapy. Serum adiponectin, soluble tumor necrosis factor receptor-2 (TNFR-2), and leptin levels were measured. Results. We compared the cases of the eight patients who underwent cranial surgery due to craniopharyngioma or prolactinoma and seven nonsurgical cases. The body mass index (surgery group, 30.2 ± 4.1; nonsurgery group, 29.2 ± 14.2) and the rate of diabetes (75% in surgery group, 14.3% in nonsurgery group) tended to be higher in the surgery group, and the hepatic fibrosis grade (surgery group, 3.75 ± 0.38; nonsurgery group, 1.64 ± 1.07) was significantly higher in the surgery group. The levels of adipocytokines, serum adiponectin, and serum soluble TNFR-2 showed no correlation with hepatic fibrosis, whereas the serum leptin levels were significantly correlated with liver fibrosis (R = 0.696). Conclusion. The hepatic fibrosis grade rapidly progressed in the cranial surgery cases of NAFLD patients with hypopituitarism, possibly in association with BMI, diabetes mellitus, and leptin. In such cranial surgery patients, strong interventions should be considered from the early stage, including diet education, hormone replacement, and more.